IMPLEMENTASI LATIHAN ANKLE STRATEGY UNTUK MENINGKATKAN KESEIMBANGAN PADA PASIEN OSTEOARTHRITIS GENU DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Cindi Anggriani; Handerman Vitu Gea; Deni Susyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Genu osteoarthritis is a degenerative disease of the knee joint that commonly occurs in older adults and may cause pain, joint stiffness, limited range of motion, and impaired balance. Balance impairment in patients with genu osteoarthritis increases the risk of falls and reduces their ability to perform activities of daily living. One of the nursing interventions that can be implemented to improve patient balance is the Ankle Strategy exercise. This study aimed to describe the implementation of Ankle Strategy exercises in patients with genu osteoarthritis at TK II Putri Hijau Hospital, Medan. This study employed a descriptive case study design involving two patients with genu osteoarthritis who experienced balance impairment. The nursing care approach included comprehensive medical-surgical nursing care consisting of assessment, nursing diagnosis, planning, implementation, and evaluation. Ankle Strategy exercises were administered for three consecutive days to enhance patients' balance and mobility. The findings demonstrated an improvement in balance among both patients following the implementation of Ankle Strategy exercises. This improvement was reflected in the patients' enhanced ability to maintain body posture, improve standing stability, and increase mobility. In the first patient, the balance score improved from 14 (poor) on the first day to 20 (good) on the second day and 26 (very good) on the third day. Similarly, the second patient's balance score increased from 14 (poor) to 19 (good) and 24 (very good) over the same period. In addition, improvements were observed in lower-extremity muscle strength, body stability, mobility, and a reduction in balance-related complaints. The intervention also contributed to a decreased risk of falls. In conclusion, the implementation of Ankle Strategy exercises had a positive effect on improving balance in patients with genu osteoarthritis and may serve as an effective non-pharmacological nursing intervention to enhance patients' functional abilities